2016
DOI: 10.1107/s2414314616006581
|View full text |Cite
|
Sign up to set email alerts
|

(4-Aminosulfonylphenyl)[(2-oxidonaphthalen-1-yl)imino]azanium

Abstract: The crystal structure of the title compound, C 16 H 13 N 3 O 3 S, shows that the two independent zwitterions in the asymmetric unit are approximately planar. Intramolecular N-HÁ Á ÁO hydrogen bonds occur and the aromatic rings have a trans configuration with respect to the azo double bond. In the crystal, the molecules are linked via N-HÁ Á ÁO hydrogen bonds and -stacking, forming a three-dimensional supramolecular network, the -stacking interactions between adjacent benzene and naphthalene rings having centro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A search for 1-phenylazo-2-naphthol derivatives in the Cambridge Structural Database (CSD; Version 2022.3.0, last update November 2022; Groom et al, 2016), revealed several examples of structurally similar azo-2-naphthol compounds prepared using different aromatic primary amines. The crystal structures of 1-[(E)-2-(5-chloro-2 hydroxyphenyl)hydrazin-1ylidene]naphthalen-2(1H)-one (Bougueria et al, 2021), (4-aminosulfonylphenyl)[(2-oxidonaphthalen-1-yl)-imino]azanium (Benosmane et al, 2016), (E)-1-(4-fluorophenyl)-2-(2-oxidonaphthalen-1-yl)diazen-1-ium (Bougueria et al, 2017) have been reported, as well as the structural and optoelec- tronic properties and theoretical investigation of a novel square-planar nickel (II) complex with an (o-tolyldiazenyl) naphthalen-2-ol ligand (Benosmane et al, 2023) that exhibits structural diversity with interesting optoelectronic properties.…”
Section: Database Surveymentioning
confidence: 99%
“…A search for 1-phenylazo-2-naphthol derivatives in the Cambridge Structural Database (CSD; Version 2022.3.0, last update November 2022; Groom et al, 2016), revealed several examples of structurally similar azo-2-naphthol compounds prepared using different aromatic primary amines. The crystal structures of 1-[(E)-2-(5-chloro-2 hydroxyphenyl)hydrazin-1ylidene]naphthalen-2(1H)-one (Bougueria et al, 2021), (4-aminosulfonylphenyl)[(2-oxidonaphthalen-1-yl)-imino]azanium (Benosmane et al, 2016), (E)-1-(4-fluorophenyl)-2-(2-oxidonaphthalen-1-yl)diazen-1-ium (Bougueria et al, 2017) have been reported, as well as the structural and optoelec- tronic properties and theoretical investigation of a novel square-planar nickel (II) complex with an (o-tolyldiazenyl) naphthalen-2-ol ligand (Benosmane et al, 2023) that exhibits structural diversity with interesting optoelectronic properties.…”
Section: Database Surveymentioning
confidence: 99%